The Impact of Public Relations on the Organization of Political Protocols in the International Relations of the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to examine the impact of public relations on the organization of political protocols in the international relations of the Kingdom of Saudi Arabia. Public relations are an effective strategic tool in improving public image and building diplomatic relations between countries. This study examines how the Kingdom uses public relations to enhance its regional and international position, as well as the impact of these protocols on political and economic relations. The study is based on a sample of 169 individuals specialized in public relations, diplomacy, and political experts, providing an in-depth and comprehensive view of the subject. The quantitative and qualitative study methodology was used to achieve the desired objectives, as data was collected through questionnaires and in-depth interviews. The results showed that public relations play a vital role in promoting political protocols and achieving the Kingdom's foreign policy goals. The importance of building integrated public relations strategies that contribute to enhancing effective communication and achieving political stability was emphasized. The study also showed that improving the Kingdom's public image enhances its international standing and contributes to achieving its political and economic goals.
Keywords: Public Relations; Political Protocols; International Relations; Saudi Arabia; Diplomatic Communication; Event Management; Social Influence